2023
DOI: 10.3390/biology12050749
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Peripheral Temperature, Sympathovagal, and Cytokine Profile in Long COVID

Abstract: A persistent state of inflammation has been reported during the COVID-19 pandemic. This study aimed to assess short-term heart rate variability (HRV), peripheral body temperature, and serum cytokine levels in patients with long COVID. We evaluated 202 patients with long COVID symptoms categorized them according to the duration of their COVID symptoms (≤120 days, n = 81; >120 days, n = 121), in addition to 95 healthy individuals selected as controls. All HRV variables differed significantly between the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Previous studies have shown the signi cance of HRV parameter reduction 39,40 and increased in ammatory parameters [41][42][43] in long-COVID individuals compared to the healthy population. Consistent with the results of this study regarding changes in the lower SDNN, TP, and VLF in the study subjects, the difference in results was not signi cant.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown the signi cance of HRV parameter reduction 39,40 and increased in ammatory parameters [41][42][43] in long-COVID individuals compared to the healthy population. Consistent with the results of this study regarding changes in the lower SDNN, TP, and VLF in the study subjects, the difference in results was not signi cant.…”
Section: Discussionmentioning
confidence: 98%
“…Another study among 318 recovered COVID-19 patients discovered that 67.8% of them reported long COVID symptoms, and those reporting long COVID symptoms had elevated levels of plasma IL-1β, IL-6, and TNF [95]. Similarly, a study in Brazil found that long COVID patients had elevated levels of IL-17 and IL-2, reduced levels of IL-4, and decreased parasympathetic nervous system activation, along with increased body temperature [96]. The authors suggested that the variations in serum IL-17, IL-4, and IL-2 seemed to represent characteristic cytokine features of long COVID, which could potentially serve as therapeutic and preventive targets.…”
Section: Unstable Cytokine Balancementioning
confidence: 94%